Data Analysis Using Cluster and Logistic Regression Analysis (A Case Study) - Byanjankar, Puspa; Marhatta, Kabindra; Himanshu, Yushma (International Journal of Information Technology and Computer Science Applications, 2023)
Customer loyalty has been a concern to C&M. C&M implements logistic regression and cluster analysis to tackle customer churn on consulting services and products. Logistic regression analysis predicts whether chemical manufacturers and small personal services will purchase consulting services and training products with discount reduction in 18 months. Their pur-chase choices every 18 months are influenced by discounts or non-discount. Cluster analysis groups purchase power based on the age group. It forecasts business client’s transaction through purchase duration and frequent purchase on consulting services and items. Thus, C&M builds a long-term relationship with chemical manufacturers and small personal ser-vices by creating customer satisfaction on our consulting services and products.